Internet connectivity disruption in Russia (Russia) - Voidly (2026)
CRITICAL severity mixed detected in Russia. Confidence: 65%. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: RU-2026-0202
Keywords: censorship; RU; mixed; critical